Aplikasi Pembelajaaran Budaya Kota Medan - Kristian Telaumbanua; Russell Russell; Eskaryono Simangunsong; Dion Izasward Sinaga (Journal of Computer System and Informatics (JoSYC), 2020)
Cultural knowledge perservation is an important aspect for every nation, the developing internet technology and globalization effect bringing modern culture merging with content that consumed by public, this issue causing ignorance about our nation cultural knowledge. With no real effort to lessen the effect of this ignorance, especially for kids that need new fresh method for delivering the knowledge can be impactful to the culture itself. The conventional direct method for delivering this cultural knowledge is limited and maybe not enough to give them concern to learn. E-learning is a new way of delivering information that can be build to fulfill our need. Fresh way to deliver the information, always updating, specific, and easy access it’s the solution we need to provide. Web Based Cultural Learning Application in Medan can provide a different approach that differ from the way conventional or school teaching, this system also provide a reward in certificates or funds as appreciation to certain participants. FAST (Framework for the Application of System Thinking) methodoloy is used to implement this system while BlackBox method functionality testing resulting a 96% fulfilled rate